El empleo según rama de actividad en el Perú y el ingreso promedio mensual proveniente del trabajo periodo 2016 – 2020 - Cruz Nuñez de Reategui, Gissel (2024)
The identification of people's income, but that comes from work, is essential to guide public policies in general, and employment generation policy in particular. This magisterial thesis aims to determine the relationship between employment according to the branch of activity in Peru and income from work, in the period 2016 - 2020. Taking it into account, we proceed to develop this Quantitative, level research. Correlational and non-experimental design. The resulting conclusions are: there is no direct relationship between employment in the Agriculture/Fishing/Mining branch of activity and the average monthly income from work, since the Correlation Coefficient was r = -0.848551101. Likewise, the largest number of workers have been working in Agriculture/Fishing/Mining, reaching the average annual figure of 4,431,889.40 people (27.18% of the total), bearing in mind that this is a primary activity and does not require skilled labor. In this same sense, it is concluded that Independent Worker is the occupation category that concentrates the largest number of employed people, reaching the number of 6,047,789.60 individuals on average, meaning 37.09%, which predominantly have been working in the informal sector. Likewise, the average income had a variable trend in the five-year period.